Cork: a strategic material. (Frontiers in chemistry, 2014)
APS

Energetic and biochemical valorization of cork boiling wastewater by anaerobic digestion. (Biotechnology for biofuels, 2014)
BACKGROUND: In addition to energy benefits, anaerobic digestion offers other interesting advantages. The cork industry is of great environmental, economic and social significance in the western Mediterranean region, with Portugal being the world-leading producer and exporter. Cork boiling wastewater (CBW) is a toxic and recalcitrant organic effluent produced by this sector, which constitutes a serious environmental hazard. However, there is no documented research on anaerobic treatment/valorization performed with this effluent. The work presented here was developed with the aim to use the anaerobic digestion process to convert the CBW polluting organic load into an energy carrier gas and valuable molecules for industry. RESULTS: No lag phases were observed and a methane yield of 0.126 to 0.142 m(3) kg(-1) chemical oxygen demand (COD)added was registered in the mesophilic consortium experiments carried out in batch flasks at 37 ± 1°C. Anaerobic digestion can be advantageously connected to ultrafiltration or electrochemical processes, due to the following: 1) reduction of ellagic acid content and consequent decrease of CBW viscosity; and 2) increase in conductivity after the anaerobic process, avoiding the electrolyte application of the electrochemical process. The improvement of several CBW biochemical features shows that anaerobic digestion may provide additionally useful molecules. The rise in concentration of some of these compounds, belonging to the benzoic acid family (gallic, protocatechuic, vanillic and syringic acids), is responsible for the increase of antiradical activity of the phenolic fraction. Additionally, some enzymatic activity was also observed and while the laccase activity increased in the digested effluent by anaerobiosis, xylanase was formed in the process. CONCLUSIONS: The multidisciplinary approach adopted allowed the valorization of CBW in terms of energy and valuable biomolecules. By exploiting the anaerobic digestion process potential, a novel methodology to toxic and recalcitrant cork processing wastewater was developed.

Relevance of genetics for conservation policies: the case of Minorcan cork oaks (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J.; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)The following values have no corresponding Zotero field: accession-num: 19671575
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber - Díaz-Fernández, Pedro M.; Climent, José; Gil, Luis (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed
Keywords: Cork oak; iberian peninsula; Phenology; quiescent flowers; ripening cycle

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed

Cork (Ullmann's Encyclopedia of Industrial Chemistry, 2000)
The article contains sections titled: 1.Introduction1.1.Definition and Origin1.2.History1.3.Morphology1.3.1.Microscopic Aspects1.3.2.Macroscopic Aspects1.4.Chemical Composition1.4.1.Suberin1.4.2.Lignin1.4.3.Polysaccharides1.4.4.Waxes1.4.5.Tannins1.4.6.Other Components1.5.Physical and Mechanical Properties2.Cork Extraction3.Production of Cork Based Products3.1.Disks and Cork Stoppers3.2.Granulates and Broken3.3.Composition Cork3.3.1.Floor and Wall Coverings3.3.2.Agglomerated Disks and Cork Stoppers3.3.3.Corkrubber3.4.Insulation Corkboard3.5.Other Specific Products4.Uses4.1.Stoppers4.2.Civil Construction4.3.Industrial Applications4.4.Automotive Industry4.5.Other Specific Uses5.Quality and Standardization5.1.Standardization and Testing5.2.Quality in Cork Production6.Economic Aspects6.1.Forestall Production6.2.Personnel and Companies6.3.Consumption of Products and Markets6.4.Producers7.Environmental and Toxicological Aspects7.1.Industrial Wastes7.2.Recycling and Treatments7.3.Emissions8.Legal Aspects

Cork - Gil, Luis; Moiteiro, Cristina (Ullmann's Encyclopedia of Industrial Chemistry, 2000)
The article contains sections titled: 1.Introduction1.1.Definition and Origin1.2.History1.3.Morphology1.3.1.Microscopic Aspects1.3.2.Macroscopic Aspects1.4.Chemical Composition1.4.1.Suberin1.4.2.Lignin1.4.3.Polysaccharides1.4.4.Waxes1.4.5.Tannins1.4.6.Other Components1.5.Physical and Mechanical Properties2.Cork Extraction3.Production of Cork Based Products3.1.Disks and Cork Stoppers3.2.Granulates and Broken3.3.Composition Cork3.3.1.Floor and Wall Coverings3.3.2.Agglomerated Disks and Cork Stoppers3.3.3.Corkrubber3.4.Insulation Corkboard3.5.Other Specific Products4.Uses4.1.Stoppers4.2.Civil Construction4.3.Industrial Applications4.4.Automotive Industry4.5.Other Specific Uses5.Quality and Standardization5.1.Standardization and Testing5.2.Quality in Cork Production6.Economic Aspects6.1.Forestall Production6.2.Personnel and Companies6.3.Consumption of Products and Markets6.4.Producers7.Environmental and Toxicological Aspects7.1.Industrial Wastes7.2.Recycling and Treatments7.3.Emissions8.Legal Aspects
The following values have no corresponding Zotero field: periodical: Ullmann's Encyclopedia of Industrial Chemistry electronic-resource-num: 10.1002/14356007.f07_f01
Keywords: composition (voyant); Cork; insulation; products; stoppers

Cork powder waste: an overview (Biomass and Bioenergy, 1997)
k powder, the major waste from cork processing industries, is generated throughout the industrial cork process and originates from grinding, cutting and finishing operations. Since there are various types of cork and different industrial operations, different types of cork powders are obtained. These have a high heating value, which make it suitable for energy production as well as other characteristics suitable for other uses as described here

Cork powder waste: an overview - Gil, Luis (Biomass and Bioenergy, 1997)
k powder, the major waste from cork processing industries, is generated throughout the industrial cork process and originates from grinding, cutting and finishing operations. Since there are various types of cork and different industrial operations, different types of cork powders are obtained. These have a high heating value, which make it suitable for energy production as well as other characteristics suitable for other uses as described here
Keywords: Cork; industry wastes; waste characterization; waste utilization